COMPUTED TOMOGRAPHY OF SMALL BOWEL OBSTRUCTION - VISRUTARATNA, Pannee; PITAKKITRONAKORN, Nongyao (The ASEAN Journal of Radiology, 2023)
Abdominal computed tomographs done between May and August 1996 of 5 patients with signs and symptoms of small bowel obstruction are reviewed. Four of these patients proved to have small bowel obstruction. The causes were adhesions (2 patients), peritoneal carcinomatosis (1 patient), and obturator hernia (1 patient). Thickening of the small bowel wall, submucosal edema of the small bowel, and ascites were seen in one of these four patients, who on surgery proved to have gangrene of the terminal ileum. On surgery the fifth patient was found to have radiation enteritis but no bowel obstruction.